A killer motive - McKinnon, Hannah Mary (Mira Books, 2025)
To Stella Dixon, sneaking her teenage brother out of their parents' house for a beach party was harmless fun--until Max disappeared without a trace. Six years later, Stella's family is still broken, and she can't let go of her guilt. The only thing that keeps her going is helping other families find closure through A Killer Motive, her true crime podcast. In a bid to find new sponsors and keep making episodes, Stella goes on a local radio show. But when she says on air that if she had just one clue, she'd find Max and bring whoever hurt him to justice, someone takes it as a challenge. A mysterious invitation to play a game arrives, with the promise that if Stella wins, she'll get information about what happened to Max. Stella thinks it's a sick joke...until Max's best friend vanishes. And she's given new instructions: tell nobody or people will die. Desperate and unable to trust anyone, Stella agrees. But beating a twisted, invisible enemy seems impossible when they make all the rules...